2019
DOI: 10.1002/ejp.1428
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention to pain cues for impending touch versus impending pain: An eye tracking study

Abstract: Background In this eye tracking study, we evaluated pain‐related biases in orienting and maintenance of gaze within impending touch versus impending pain tasks and examined features of pain resilience as individual difference influences on potential biases. Methods Gaze preferences of healthy adults (25 women and 39 men) were assessed during standardized pain‐neutral (P‐N) image pair presentations (2,000 ms) of an impending touch task versus an impending pain task whereby image pair offsets were followed by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 26 publications
6
24
1
1
Order By: Relevance
“…One study provided evidence for an initial orienting bias (i.e., more first fixations) towards sensory pain words in healthy adults with high fear of pain compared to those with low fear of pain (Yang et al, 2012) but three other studies found no fear of pain effects on orienting (Jackson et al, 2018b;Sharpe et al, 2017;Yang et al, 2013). In six studies that investigated effects of threat on first fixation proportion, three found that first EYE MOVEMENTS AND PAIN 15 fixation proportion on pain-related stimuli was reduced by the threat of pain (d = 0.26-0.84) (Jackson et al, 2018a(Jackson et al, , 2018bSharpe et al, 2017), while one found a complementary effect (d = 0.32) (Ling et al, 2019), and two others found no effect (Schoth, Wu, et al, 2019;.…”
Section: First Fixation Proportionmentioning
confidence: 97%
See 2 more Smart Citations
“…One study provided evidence for an initial orienting bias (i.e., more first fixations) towards sensory pain words in healthy adults with high fear of pain compared to those with low fear of pain (Yang et al, 2012) but three other studies found no fear of pain effects on orienting (Jackson et al, 2018b;Sharpe et al, 2017;Yang et al, 2013). In six studies that investigated effects of threat on first fixation proportion, three found that first EYE MOVEMENTS AND PAIN 15 fixation proportion on pain-related stimuli was reduced by the threat of pain (d = 0.26-0.84) (Jackson et al, 2018a(Jackson et al, , 2018bSharpe et al, 2017), while one found a complementary effect (d = 0.32) (Ling et al, 2019), and two others found no effect (Schoth, Wu, et al, 2019;.…”
Section: First Fixation Proportionmentioning
confidence: 97%
“…Moreover, first fixation durations on pain-related stimuli are not influenced by fear of pain (Sharpe et al, 2017;Yang et al, 2012Yang et al, , 2013, pain-related threatening instructions on a separate task (Sharpe et al, 2017;Sun et al, 2016;, or experimental thermal pain prior to a dot-probe task (Sun et al, 2016). However, in two studies of pain-free participants that featured pain-related images signalling possible electric pain versus neutral images signalling its absence, first fixation durations for pain-related images were significantly longer (d = 0.47-0.58) (Jackson et al, 2018a;Ling et al, 2019).…”
Section: First Fixation/visit Durationmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, more challenging cognitive tasks such as the high difficulty NIT condition reflected resilience (and resilience subgroup differences) more clearly than did the less demanding, lower difficulty (i.e., lower adversity) condition that reflected resilience only weakly. Results from recent eye‐tracking research align with these contentions in that resilience was found to correlate with the capacity to disengage more easily from pain images in a more demanding task that featured painful stimulation but was not correlated with disengagement capacities in a less demanding task that involved nonpainful touch stimuli (Ling, Yang, & Jackson, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…Meta-analyses based on RT have provided selective support for this premise based on stronger ABs towards sensory pain words in chronic pain groups relative to controls (Crombez et al, 2013;Todd et al, 2018), albeit mean effect sizes have been small, and do not extend reliably to other stimulus categories. Extensions based on eye-tracking have found that the threat of impending pain is associated with prolonged attention towards cues that signal the threat of potential pain compared to cues that signal its absence (Jackson, Su, & Wang, 2018a, 2018bLing, Yang, & Jackson, 2019).…”
Section: Discussionmentioning
confidence: 99%